2010
DOI: 10.1186/1471-2164-11-715
|View full text |Cite
|
Sign up to set email alerts
|

miRNeye: a microRNA expression atlas of the mouse eye

Abstract: BackgroundMicroRNAs (miRNAs) are key regulators of biological processes. To define miRNA function in the eye, it is essential to determine a high-resolution profile of their spatial and temporal distribution.ResultsIn this report, we present the first comprehensive survey of miRNA expression in ocular tissues, using both microarray and RNA in situ hybridization (ISH) procedures. We initially determined the expression profiles of miRNAs in the retina, lens, cornea and retinal pigment epithelium of the adult mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
123
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 54 publications
(53 reference statements)
11
123
0
1
Order By: Relevance
“…The developmental increase in expression of miR-9, miR125b, and let-7 family members that we observe in the retinal progenitors confirms and extends earlier analyses of retinal miRNAs (31)(32)(33)(34)(35)(36). The most recent comprehensive microarray and in situ analyses (31,35) show that miR-9, miR-125, and several members of the let-7 family (including let-7a, -b, -c, -d, -e, -f, -g, and -i) are expressed in the retina and increase over the developmental period that we have analyzed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The developmental increase in expression of miR-9, miR125b, and let-7 family members that we observe in the retinal progenitors confirms and extends earlier analyses of retinal miRNAs (31)(32)(33)(34)(35)(36). The most recent comprehensive microarray and in situ analyses (31,35) show that miR-9, miR-125, and several members of the let-7 family (including let-7a, -b, -c, -d, -e, -f, -g, and -i) are expressed in the retina and increase over the developmental period that we have analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, previous in situ localization studies have demonstrated that there is widespread expression of let-7 family members in all retinal layers from E16.5 to adulthood (ref. 33; http://mirneye.tigem.it), and miR-9 is expressed from optic cup stages to all retinal layers at P0 (33,35). Our results now show that several members of the let-7 family, miR-9, and miR-125 increase quantitatively over the period of retinal development when the progenitors change their competence, consistent with the hypothesis that miRNAs regulate this process.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…First, we performed miRNA array profiling of 84 miRNAs that have been assigned a role in vascular function and/or dysfunction. Overall, microarray results shown in Table 1 were concordant with previous surveys of the miRNA expression pattern in the retina using either microarrays or deep sequencing technologies (5,32). Several miRNAs with stricter cut-off criteria (log 2 Ͼ2 or ϽϪ2) were differentially expressed at P12 following hyperoxiainduced vaso-obliteration, including miR-103, miR-107, miR-125, miR-126, miR-155, miR-93, miR-16, and miR-195.…”
Section: Microrna Expression Profile In the Retina Of Oir Mice-supporting
confidence: 85%
“…The loss of ERG b-wave in KO mice indicated abnormalities at either pre-or postsynaptic levels. Previous studies detected the three miRNAs of the cluster in bipolar and ganglion cells in addition to photoreceptors (9,17). To resolve which cell populations are affected in the KO, retinas from adult wild-type Fig.…”
Section: Maturation Deficiency Of Cone and Rod Pathways As Measured Bymentioning
confidence: 99%